Impact of disposable packaging in automotive production - Blomberg, Anna; Hallams, Gabriella (My University, 2017)
Studies shows that the future packaging trends in the automotive industry are turning towards an increased usage of disposable packaging in longer distance flows. Accordingly, Volvo Group has initiated a project called Next Generation Packaging with the objective to harmonize and standardize the Volvo Group’s packaging pool. However, there are concerns that disposable packaging material (often cardboard) will have a negative impact on the material handling, scrapping or recycling, and the level of cleanliness inside production plants, thus affecting the production quality. The aim of this thesis is to study the effects of an increased usage of disposable packaging in the Volvo Group’s receiving plant from goods receiving to point of use to waste handling, and to identify potential problems that arise from replacing the returnable packaging with disposable alternatives. The total scope for the project Next Generation Packaging is global, but the master thesis is limited in terms of geographical location and the main focus is on the production plant in Tuve. The report will further be limited to the packaging alternatives that Next Generation Packaging is reviewing, which are disposable boxes and pallets in cardboard provided by Papyrus Supplies. In order to fulfil the aim and answer the research questions, an extensive part of the study was to understand and to map the current state of Volvo Group’s internal logistics processes by conducting a Material Flow Mapping. The flows decided to follow were two pallet flows and four box flows. The six flows together covered all logistics processes that the disposable packaging needed to be tested in, in order to ensure endurance and applicability before a possible implementation. To evaluate the packaging performance, the disposable packaging alternative provided by Papyrus Supplies have been analysed from four different packaging requirements: the protective perspective, the handling efficiency perspective, the ergonomic perspective, and the information perspective. The main conclusions made from analysing the disposable packaging based on these four perspectives are that the disposable packaging solutions could, in the rough, be handled in the same internal logistics processes up to the handling and collection of empty packaging. The breakdown of empty cardboard packaging does require new processes, as well as space and locations for handling of empty packaging.
Keywords: Transport; Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics